2011
DOI: 10.1016/j.aquaculture.2010.05.030
|View full text |Cite
|
Sign up to set email alerts
|

A review of the broodstock management and larviculture of the Pacific northern bluefin tuna in Japan

Abstract: We reviewed research on the broodstock management and larviculture of the Pacific northern bluefin tuna (PBT) Thunnus orientalis in Japan. Japan has been at the forefront of PBT research since 1970 due to the participation by federal and prefectural governments and universities in a national project aimed to optimize productivity of the sea around Japan. In 1979, scientists at Kinki University succeeded in the first spontaneous spawning in captivity by the broodstock of 5 year-old PBT. Successful spawning was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 26 publications
1
45
0
1
Order By: Relevance
“…Pacific bluefin tuna has high market value, but wild populations have decreased in recent years [1]. The complete lifecycle of this species has been closed for aquaculture, and artificial seed is being used for production [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pacific bluefin tuna has high market value, but wild populations have decreased in recent years [1]. The complete lifecycle of this species has been closed for aquaculture, and artificial seed is being used for production [2].…”
Section: Discussionmentioning
confidence: 99%
“…However, tuna catch is restricted by international fishing regulations created as a result of recent decreases in wild population numbers [1]. Thus, a breeding system that depends on the recruitment of naturally occurring siblings is difficult to maintain.…”
Section: Introductionmentioning
confidence: 99%
“…Although having a larger number of families decreased inbreeding, in practical situations the number of families almost always will be a significant limiting factor due to biological, physical and cost constraints on the number of spawning parent brood stock available, as well as the size and number of tanks and the costs of rearing and evaluating the families (Coman and Henshall, 2010;Masuma et al, 2010). In particular, the similarity in levels of genetic gain across varying numbers of families is of interest as it showed that meeting the relatedness constraint with smaller numbers of families only requires a trade-off with lower levels of genetic gain when numbers of families are low (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are a number of challenges in establishing and maintaining breeding programmes in aquaculture species, and this is particularly so for new species where control of the full life cycle in captivity can be challenging (e.g. Fauvel et al, 2008;Masuma et al, 2010). Small juvenile size means that families are often reared separately until they are of sufficient size for individual tagging.…”
Section: Introductionmentioning
confidence: 99%
“…Hal ini dapat terjadi karena persentasi jumlah induk yang baru pertama kali memijah masih sedikit (Masuma, 2006). Laju pematangan gonad dan pemijahan induk dalam kolam atau jaring lebih rendah dibandingkan di alam bebas (Seoka et al, 2008).…”
Section: Hasil Dan Bahasanunclassified